GENETIC DISCRIMINATION AS THE INFRINGEMENT ON THE RIGHTS AND INTERESTS OF A PERSON - Koterlin, О. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The author of the article studies the genetic discrimination as the infringement on the rights and interests of a person. The attention is focused on the types of discrimination as well as on legal grounds to counteract this discrimination. The author analyses the lawful situation in Ukrainian legislature.